QRIS PAYMENT METHOD AS A SOLUTION FOR GEN Z TO EASIER FINANCIAL TRANSACTIONS - Totok Kurniawan (JINGJI : Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
Continuous improvements in infrastructure, security measures, and user education can help address these weaknesses and increase the overall effectiveness of QRIS as a digital payment solution. One of the key benefits of QRIS among millennials is convenience. QRIS makes it easy for millennials to make digital payments without carrying cash or credit/debit cards. They simply use their mobile phones to scan a QR code and complete the transaction. QRIS transactions are processed in real time, meaning payments can be completed almost instantly. Many digital payment platforms that support QRIS offer promotions and discounts to users who make payments using their platforms. This is especially appealing to millennials who are always looking for ways to save money.